Nations at dawn : - Stoessinger, John George (McGraw-Hill, 1994)
This edition significantly reworks material on the former Soviet Union. Stoessinger chronicles the undoing of the Soviet Union and relates its ongoing efforts at the establishing of a true democracy while also reexamining China's "Old Guard" and speculating on the emergence of new forces and new directions there.